Comparison of Two Fast MRI Methods for Perfusion Imaging of the Heart - Sijens, P. E.; Lubbers, D. D. (Imaging decisions MRI, 2009)
Summary Time‐adaptive sensitivity encoding (TSENSE) and generalized autocalibrating partially parallel acquisition (GRAPPA) were applied to a gradient‐echo sequence used for first‐pass myocardial perfusion imaging of 12 patients with coronary artery disease. The two parallel imaging methods were compared in terms of signal‐to‐noise ratio (SNR), contrast‐to‐noise ratio (CNR) and image artefacts. Image acquisition was started during the administration of a Gd‐contrast bolus (0.1 mmoL/kg) followed by a 20‐mL saline flush (3 mL/s), and the next perfusion was started at least 15 min thereafter using an identical bolus. The order of perfusion sequences was inverted in every other patient. Both acquisitions had an acceleration rate of 2, and were performed during breath‐holding. The SNR, CNR and image quality of the GRAPPA images were significantly better than were those of the TSENSE images. An exception was the lower CNR of GRAPPA when applied after the second bolus. Differences between subjects were larger with GRAPPA perfusion imaging than with TSENSE. The SNR and CNR also varied relatively much between the GRAPPA images, indicating that the diagnostic value of TSENSE may be superior after all.